Assessing the Impact of Work-Integrated Learning on Business Education Students' Employability in College of Education in Nigeria - Jamilu, Usman Mohammed; Paris, Suleiman Adama; Sambo, Gidado Farida (Lembaga Yasin AlSys, 2024)
This study assessed the impact of Work-Integrated Learning (WIL) programs on the employability of business education students in Colleges of Education in Nigeria. The study adopted a descriptive survey research design, with a sample of 240 respondents, including administrators, teachers, and students, from selected Colleges of Education. Data were collected using a structured questionnaire and analyzed using mean statistics. The findings revealed that WIL programs are moderately implemented in business education curricula, contributing significantly to the development of employability skills such as communication, teamwork, and problem-solving. However, challenges such as limited internship placements, insufficient collaboration with industries, and financial constraints hinder students’ access to WIL opportunities. The study recommended strengthening partnerships between colleges and industries, making WIL mandatory in business education programs, providing financial support to students, and enhancing supervision and mentorship during WIL placements.